Thermal Runaway Detection Method for Smart Electric Bicycle Charger - Jing Ning; Bing Xiao; Wenbin Zhao (Engineering Reports, 2025)
ABSTRACT A novel algorithm for thermal runaway detection embedded in the electric bicycle charging system is proposed. The battery's internal temperature is a key indicator to diagnose battery safety and monitor the charging state. First, the relationship between the battery's internal temperature and the impedance's phase shift is derived theoretically. Second, given that random interference in the charging current, the current area integration algorithm (CAIA) is presented to measure the phase shift, so the internal temperature is estimated. Third, the smart charging system for electric bicycles is presented and results are discussed. The results show that the phase shift increases with the internal temperature in the range of 200–600 Hz when the internal temperature is 20°C–35°C. When the internal temperature reaches 45°C, the phase shift decreases sharply with the internal temperature. Therefore, smart electric bicycle charger realizes thermal runaway detection of electric bicycle.